A theoretical investigation on the neutral Cu(I) phosphorescent complexes with azole-based and phosphine mixed ligand. (18th April 2018) - Ding, Xiao-Li; Shen, Lu; Zou, Lu-Yi; Ma, Ming-Shuo; Ren, Ai-Min
ABSTRACT: A theoretical study on a series of neutral heteroleptic Cu(I) complexes with different azole-pyridine-based N^N ligands has been presented to get insight into the effect of various nitrogen atoms in the azole ring on photophysical properties. The results reveal that the highest occupied molecular orbital (HOMO) levels and the emission wavelengths of these complexes are mainly governed by the nitrogen atom number in azole ring. With the increasing number of nitrogen atom, the electron density distribution of HOMO gradually extend from the N^N ligand to the whole molecule, meanwhile, the improved contribution from Cu(d) orbits in HOMO results in an effective mixing of various charge transfermodes, and hence, the fast radiative decay(kr) and the slow non-radiative decay rate(knr) are achieved. The photoluminescence quantum yield (PLQY) show an apparent dependence on the nitrogen atom number in the five-membered nitrogen heterocycles. However, the increasing number of nitrogen atoms is not necessary for increasing PLQY. The complex 3 with 1, 2, 4-triazole-pyridine-based N^N ligands is considered to be a potential emitter with high phosphorescence efficiency. Finally, we hope that our investigations will contribute to systematical understanding and guiding for material molecular engineering. Abstract :